Makna Simbolik Barang Persembahan Pada Altar Dewa-Dewi Di Kelenteng Liong Hok Bio Kota Magelang - Agus Subandi (Vijjacariya: Jurnal Pemikiran dan Pendidikan Buddhis, 2021)
The offerings at the gods altar in the Liong Hok Bio temple consisted of various drinks and foods. These offerings will be periodically replaced with new offerings. This study aimed to describe the form of offerings on the gods altar in the Liong Hok Bio temple, Magelang City and analyze the symbolic meaning of the offerings at the gods altar in the Liong Hok Bio temple, Magelang City. This research used a qualitative study approach with case study model. The results showed that the form of offerings at the gods altar in the Liong Hok Bio temple, Magelang City were the objects which placed at the altar. The symbolic meaning which presented at the gods altar in the Liong Hok Bio temple, Magelang City was as a form of worshiping ancestors and gods, but in practice everything goes according to the karma that has been done, and the request will be reached if the good karma has supported.